2007
DOI: 10.1007/s00464-007-9298-5
|View full text |Cite
|
Sign up to set email alerts
|

The influence of experience and camera holding on laparoscopic instrument movements measured with the TrEndo tracking system

Abstract: Background: Eye-hand coordination problems occur during laparoscopy. This study aimed to investigate the difference in instrument movements between the surgeon him-or herself holding the camera and an assistant holding the camera during performance of a laparoscopic task and to check whether experience of the surgeon plays a role in this issue. Methods: The participants were divided into three groups: experts, residents, and novices. Each participant performed positioning tasks using the right (R) and left (L)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 15 publications
1
40
1
1
Order By: Relevance
“…A possible reason for this may reside in the post-processing stage of EVA, which effectively applies low pass filtering of the signal in ways that may dampen the influence of jerkiness in movements. It is important to mention that for both systems motion smoothness did not achieve construct validation and that this particular metric has been already been proved not valid for several basic tasks [42,43]. EVA showed good construct validity both for 2D and 3D metrics.…”
Section: Discussionmentioning
confidence: 87%
“…A possible reason for this may reside in the post-processing stage of EVA, which effectively applies low pass filtering of the signal in ways that may dampen the influence of jerkiness in movements. It is important to mention that for both systems motion smoothness did not achieve construct validation and that this particular metric has been already been proved not valid for several basic tasks [42,43]. EVA showed good construct validity both for 2D and 3D metrics.…”
Section: Discussionmentioning
confidence: 87%
“…In the literature, it is demonstrated that time, path length, and depth perception can distinguish between different levels of performance, based on the instrument movements [13,14]. Moreover, these three parameters are commonly used to (automatically) assess the performance of laparoscopic training tasks.…”
Section: Introductionmentioning
confidence: 99%
“…Thirteen metrics were used for the evaluation of the performance of all the participants (Table 1) [25,[31][32][33]. All motion metrics were computed using Matlab Release 2012a (Mathworks, Natick, MA).…”
Section: Construct Validitymentioning
confidence: 99%